Doxycycline induced pill oesophagitis: A case report - Duwadee, Prabin; Dhungana, Reechashree; Shrestha, Pratick; Sharma, Suraj; Aryal, Sajiva (Journal of Chitwan Medical College, 2025)
Doxycycline, along with other medications such as nonsteroidal anti-inflammatory drugs, tetracycline, and bisphosphonates, is notorious for causing pill-induced mucosal injury of the oesophagus. It usually manifests as retrosternal chest pain, dysphagia, and odynophagia following ingestion of an offending medication. Endoscopy shows multiple ulcers on the oesophagus. Treatment involves discontinuation of the offending agent, intravenous fluids, PPIs, and sucralfate solution. Resolution of symptoms occurs within 7-10 days of treatment. Proper counselling before prescribing such medications and applying preventive measures after consuming such medications reduces adverse outcomes. We report a case of a lady of 25 years who presented with pill-induced oesophagitis after oral Doxycycline prescribed for Brucellosis. Retrosternal burning, painful with difficulty in swallowing and endoscopy findings of oesophageal ulcer confirmed the diagnosis. She was successfully managed with switching oral to intravenous Doxycycline, proton pump inhibitor, sucralfate and other conservative management.